On ERPs detection in disorders of consciousness rehabilitation - Risetti, Monica; Formisano, Rita; Toppi, Jlenia; Quitadamo, Lucia Rita; Bianchi, Luigi; Astolfi, Laura; Cincotti, Febo; Mattia, Donatella (Frontiers in Human Neuroscience, 2013)
Disorders of Consciousness (DOC) like Vegetative State (VS) and Minimally Conscious State (MCS) are clinical conditions characterized by the absence or intermittent behavioural responsiveness. A neurophysiological monitoring of parameters like Event-Related Potentials (ERPs) could be a first step to follow-up the clinical evolution of these patients during their rehabilitation phase. Eleven patients diagnosed as VS (n= 8) and MCS (n= 3) by means of the JFK Coma Recovery Scale Revised (CRS-R) underwent scalp EEG recordings during the delivery of a 3-stimuli auditory oddball paradigm, which included standard, deviant tones and the subject own name (SON) presented as a novel stimulus, administered under passive and active conditions. Four patients who showed a change in their clinical status as detected by means of the CRS-R (i.e moved from VS to MCS), were subjected to a second EEG recording session. All patients, but one (anoxic etiology), showed ERP components such as mismatch negativity (MMN) and novelty P300 (nP3) under passive condition. When patients were asked to count the novel stimuli (active condition), the nP3 component displayed a significant increase in amplitude (p = .009) and a wider topographical distribution with respect to the passive listening, only in MCS. In 2 out of the 4 patients who underwent a second recording session consistently with their transition from VS to MCS, the nP3 component elicited by passive listening of SON stimuli revealed a significant amplitude increment (p